A collaborative sequential meta‐analysis of individual patient data from randomized trials of endovascular therapy and tPA vs. tPA alone for acute ischemic stroke: ThRombEctomy And tPA (TREAT) analysis: statistical analysis plan for a sequential meta‐analysis performed within the VISTA‐Endovascular collaboration. (9th September 2015) - MacIsaac, Rachael L.; Khatri, Pooja; Bendszus, Martin; Bracard, Serge; Broderick, Joseph; Campbell, Bruce; Ciccone, Alfonso; Dávalos, Antoni; Davis, Stephen M.; Demchuk, Andrew; Diener, Hans‐Christoph; Dippel, Diederik; et al.
Abstract : Rationale: Endovascular treatment has been shown to restore blood flow effectively. Second‐generation medical devices such as stent retrievers are now showing overwhelming efficacy in clinical trials, particularly in conjunction with intravenous recombinant tissue plasminogen activator. Aims and Design: This statistical analysis plan utilizing a novel, sequential approach describes a prospective, individual patient data analysis of endovascular therapy in conjunction with intravenous recombinant tissue plasminogen activator agreed upon by the Thrombectomy and Tissue Plasminogen Activator Collaborative Group. Study Outcomes: This protocol will specify the primary outcome for efficacy, as 'favorable' outcome defined by the ordinal distribution of the modified Rankin Scale measured at three‐months poststroke, but with modified Rankin Scales 5 and 6 collapsed into a single category. The primary analysis will aim to answer the questions: 'what is the treatment effect of endovascular therapy with intravenous recombinant tissue plasminogen activator compared to intravenous tissue plasminogen activator alone on full scale modified Rankin Scale at 3 months?' and 'to what extent do key patient characteristics influence the treatment effect of endovascular therapy?'. Key secondary outcomes include effect of endovascular therapy on death within 90 days; analyses of modified Rankin Scale using dichotomized methods; and effects of endovascular therapy on symptomatic intracranial hemorrhage. Several secondary analyses will be considered as well as expanding patient cohorts to intravenous recombinant tissue plasminogen activator‐ineligible patients, should data allow. Discussion: This collaborative meta‐analysis of individual participant data from randomized trials of endovascular therapy vs. control in conjunction with intravenous thrombolysis will demonstrate the efficacy and generalizability of endovascular therapy with intravenous thrombolysis as a concomitant medication.